Rewarding Sequential Innovators: Prizes, Patents, and Buyouts - Hopenhayn, Hugo; Llobet, Gerard; Mitchell, Matthew (Journal of Political Economy, 2006)
This paper presents a model of cumulative innovation in which firms are heterogeneous in their research ability. We study the optimal reward policy when the quality of the ideas and their subsequent development effort are private information. Monopoly power is a scarce resource to be allocated across innovators who arrive at various times. The optimal assignment of property rights must counterbalance the incentives of current and future innovators. The resulting mechanism resembles a menu of patents that have infinite duration and fixed scope. This optimal patent menu can be implemented with a simple buyout scheme: The innovator commits at the outset to a price ceiling at which he will sell his rights to a future inventor. When a larger fee is paid initially, a higher price ceiling is obtained. Any subsequent innovator must pay this price and purchase his own buyout fee contract. We relate this mechanism to the proposed compulsory licensing schemes.